PRA-RANCANGAN PABRIK AMMONIUM KLORIDA DARI AMMONIUM SULFAT DAN NATRIUM KLORIDA KAPASITAS 32.000 TON/TAHUN - , CAHYA SETIAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Ammonium Chloride (NH4Cl) is chemicals material that is much used in the chemical industries. Ammonium chloride is used as a raw material for the batteries manufacture, cleaning solder for electronics industry, plywood glue, hardener snow, fertilizer, and the material for alkylhydroxylamine nitroparaffin reduction. NH4Cl production done by methatesis method (NH4)2SO4-NaCl were proceded by a process of purification of salt to become pure grade NaCl. NaCl and (NH4)2SO4 is dissolved in water in a reactor at a temperature of 30Â°C and a pressure of 1 atm. After exiting the reactor is formed NH4Cl solution and supersaturated solution of Na2SO4 which later crystallized in the Crystallizer. NH4Cl plant is classified as low risk due to plant operating conditions and the material used is safe for the environment. The whole process is done in the room due to the nature of materials that easily absorb water. NH4Cl factory is planned to be constructed in Gresik, East Java with a total area of Â± 7.5 ha of land and required 225 labours. The plant was designed with the capacity of 32,000 tons / year and operates continuously for 330 days / year. Ammonium chloride to produce as much as 3,616.25 kg/h of fuel, needed fuel oil as much as 1277.26 kg/h, the water needs of the river as much as 12,6905 m3/h, electricity needs 1019.89 kW and the needs of a total of 16660.71 kg of steam/h. Fixed capital required $ 6,452,181.43 and Rp 215,931,928,424.65 and working capital required Rp 144,213,953,047.49, with profit before tax Rp 93,919,677,175.13 and Rp 46,959,838,587.57 after tax. From the calculation results obtained by Return on Investment (ROI) before taxes 34.28% and 17.14% after tax, Pay Out Time (POT) before tax 2.25 years and 3.68 years after tax, Break Even Point (BEP) 49%. Shut Down Point (SDP) 28.13% and Discounted Cash Flow of Return (DCFRR) 35.48%. Based on that NH4Cl plant is quite interesting to study further.